2019
DOI: 10.1007/s12024-018-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Relevant findings on postmortem CT and postmortem MRI in hanging, ligature strangulation and manual strangulation and their additional value compared to autopsy – a systematic review

Abstract: Several articles have described the use of postmortem computed tomography (CT) and postmortem magnetic resonance imaging (MRI) in forensic medicine. Although access to CT scanners and, particularly, access to MRI scanners, is still limited for several institutes, both modalities are being applied with increasing frequency in the forensic setting. Certainly, postmortem imaging can provide crucial information prior to autopsy, and this method has even been considered a replacement to autopsy in selected cases by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 59 publications
(117 reference statements)
1
21
0
9
Order By: Relevance
“…In the present case, postmortem MRI was not only able to visualize the soft tissue injuries better than CT, as frequently mentioned in the literature , but also enabled the visualization of the wound channel without obfuscation by metal artifacts, as was the case on CT. A gunshot wound with a lodged bullet may reduce the diagnostic value of CT. The radiologic assessment of gunshot injuries can be severely impeded on CT due to metal artifacts caused by the lodged bullet; thus, an MRI examination may be of particular value for such nonperforating gunshot wounds.…”
Section: Discussionsupporting
confidence: 70%
“…In the present case, postmortem MRI was not only able to visualize the soft tissue injuries better than CT, as frequently mentioned in the literature , but also enabled the visualization of the wound channel without obfuscation by metal artifacts, as was the case on CT. A gunshot wound with a lodged bullet may reduce the diagnostic value of CT. The radiologic assessment of gunshot injuries can be severely impeded on CT due to metal artifacts caused by the lodged bullet; thus, an MRI examination may be of particular value for such nonperforating gunshot wounds.…”
Section: Discussionsupporting
confidence: 70%
“…Intramuscular hemorrhages are the most prominent collateral injury in cases of ligature and manual strangulation Most data about injuries in strangulation are obtained from hanging. [1][2][3] Certain characteristic traumatic injuries have been described throughout the years. Laryngeal fractures are a common injury in addition to soft tissue lesions, such as subcutaneous, intramuscular, and lymph node, and glandular hemorrhages and swellings.…”
mentioning
confidence: 99%
“…1,13,14 During the process of strangulation, neck injuries occur frequently, which can be visualized by computed tomography (CT), magnetic resonance imaging (MRI), or autopsy. 3,[15][16][17][18][19] According to these studies, intramuscular hemorrhages and subcutaneous bleeding are considered important indicators of severity. In those studies, MRI showed a significant value in detecting these injuries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the review article by Dominic Gascho et al [1] about relevant findings on post-mortem total body CT (TBCT)/MRI in cases of strangulation. The authors describe fracture patterns and hemorrhages in strangulation cases, but they admit that large-scale studies for relevant findings on CT and MRI related to strangulation are lacking.…”
mentioning
confidence: 99%